Adolescent and young adult cancers: unmet needs and closing the gaps. Issue 1 (11th February 2023) - Berkman, Amy M.; Mittal, Nupur; Roth, Michael E.
Abstract : Purpose of review: There is a growing population of adolescent and young adult (AYA, ages 15–39 years) cancer patients and survivors, and the field of AYA oncology is rapidly evolving. Despite an increased focus on survival and quality of life for AYAs, gaps in knowledge remain. The current review focuses on what is known across several domains unique to AYA cancer care as well as areas of improvement and future directions in research and intervention. Recent findings: Due to the developmental stages included in the AYA age range, a cancer diagnosis and treatment can affect relationships, education and employment, finances, and long-term health differently than diagnoses in younger or older populations. Recent studies that have focused on these unique aspects of AYA cancer care, including health-related quality of life (HRQoL), fertility, financial toxicity, barriers to clinical trial enrollment, genetic predisposition, and survivorship care are included in the current review. Summary: Although studies have described many of the challenges faced by AYAs across the cancer continuum from diagnosis to survivorship, more work is needed, particularly in systematically measuring HRQoL, eliminating barriers to clinical trial enrollment, addressing financial toxicity, and increasing access to fertility preservation and high-quality survivorship care.